Developments in classroom-based research on L2 writing - Icy Lee (Studies in Second Language Learning and Teaching, 2022)
This paper reviews and reflects on developments in classroom-based research on second or foreign language (L2) writing from 2001 to 2020, based on scholarship drawn from the Journal of Second Language Writing, the flagship journal of the field. The review covers a total of 75 classroom-based studies and examines the major research themes and key findings under three research strands: (1) students and student learning of writing; (2) teachers and teaching of writing; and (3) classroom assessment and feedback, as well as the key theories and research methodologies adopted in extant classroom-based studies on L2 writing. The article ends with a discussion of the practical implications arising from the review, as well as potential research gaps that inform future directions for L2 writing classroom-based research. By providing a state-of-the-art review of developments in classroom-based research on L2 writing, this article contributes to a nuanced understanding of salient issues about learning, teaching and assessment of writing that take place in naturalistic classroom contexts, with relevant implications for both L2 writing practitioners and researchers.